Placenta percreta associated with placenta previa and abruptio: A case report (2015)
The number of cesarean sections has risen during the recent years, leading to an increase in abnormal placentation in future pregnancies, as well as other materno-fetal complications. Placental abnormalities and the surgical management they usually required, drastically obscure maternal and fetal outcomes. We report the case of a multiparous woman admitted to labor and delivery service of a university hospital presenting with placenta percreta, placenta previa and abruptio placentae. She received opportune emergency multidisciplinary management, obtaining satisfactory. © 2013 SEGO.